Molecular Bases of Cutaneous and Uveal Melanomas. (18th August 2011) - Gaudi, Sudeep; Messina, Jane L.
Abstract : Intensive research in recent years has begun to unlock the mysteries surrounding the molecular pathogenesis of melanoma, the deadliest of skin cancers. The high-penetrance, low-frequency susceptibility gene CDKN2A produces tumor suppressor proteins that function in concert with p53 and retinoblastoma protein to thwart melanomagenesis. Aberrant CDKN2A gene products have been implicated in a great many cases of familial cutaneous melanoma. Sporadic cases, on the other hand, often involve constitutive signal transduction along the mitogen-activated protein kinase (MAPK) pathway, with particular focus falling upon mutated RAS and RAF protooncogenes. The proliferative effects of the MAPK pathway may be complemented by the antiapoptotic signals of the PI3K/AKT pathway. After skin, melanoma most commonly affects the eye. Data for the constitutive activation of the MAPK pathway in uveal melanoma exists as well, however, not through mutations of RAS and RAF. Rather, evidence implicates the proto-oncogene GNAQ. In the following discussion, we review the major molecular pathways implicated in both familial and sporadic cutaneous melanomagenesis, the former accounting for approximately 10% of cases. Additionally, we discuss the molecular pathways for which preliminary evidence suggests a role in uveal melanomagenesis.